2013
DOI: 10.1371/journal.pone.0064133
|View full text |Cite
|
Sign up to set email alerts
|

Home Life: Factors Structuring the Bacterial Diversity Found within and between Homes

Abstract: Most of our time is spent indoors where we are exposed to a wide array of different microorganisms living on surfaces and in the air of our homes. Despite their ubiquity and abundance, we have a limited understanding of the microbial diversity found within homes and how the composition and diversity of microbial communities change across different locations within the home. Here we examined the diversity of bacterial communities found in nine distinct locations within each of forty homes in the Raleigh-Durham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
329
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(348 citation statements)
references
References 55 publications
19
329
0
Order By: Relevance
“…In particular, whether a home had dogs was the most important predictor of the relative abundances of those bacteria preferentially found within homes (electronic supplementary material, table S2). This effect of dogs on indoor bacterial communities has been noted previously [3,20,22] with some work suggesting that these bacterial differences are associated with human health outcomes rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: (B) Strong Influence Of the Outdoor Environment On Indoor Fungisupporting
confidence: 62%
See 1 more Smart Citation
“…In particular, whether a home had dogs was the most important predictor of the relative abundances of those bacteria preferentially found within homes (electronic supplementary material, table S2). This effect of dogs on indoor bacterial communities has been noted previously [3,20,22] with some work suggesting that these bacterial differences are associated with human health outcomes rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: (B) Strong Influence Of the Outdoor Environment On Indoor Fungisupporting
confidence: 62%
“…If there was ever any doubt, it has become clear in recent years that we are exposed to many thousands of bacterial and fungal species as we go about our daily lives [1][2][3][4]. As humans become ever-more urban and we now spend the majority of our lives indoors [5], the time we spend with the microbial taxa found inside homes is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of similarities (ANOSIM) test was performed in PRIMER (v.6; PRIMER-E, Plymouth, United Kingdom) to determine whether the major sample factors (MTR line, MTR line type, indoors/outdoors, time, peak/nonpeak, sampling day) had significantly different microbial communities. UniFrac distance calculations, PCoA, and ANOSIM were also performed to compare microbial communities from our study to indoor samples collected from air and surface samples from previous reports (5,36). These reports were selected because they targeted the same V4 16S rRNA gene region using the Illumina sequencing platform.…”
Section: Mtrmentioning
confidence: 99%
“…As one of the few large-scale studies investigating aerosol microbial community composition in Asia, we were interested in comparing our subway and outdoor data sets to those of indoor microbiome studies conducted elsewhere. We have chosen studies investigating the bioaerosols of a university building in Oregon (36) and the household surface microbial compositions in North Carolina homes (5). PCoA plots based on weighted UniFrac distances clearly showed that the Hong Kong cluster is distinct from the American groups (global R ϭ 0.34, P ϭ 0.001 by ANOSIM) (Fig.…”
Section: ϫ10mentioning
confidence: 99%
See 1 more Smart Citation